Exposure to Political Disparagement Humor and Its Impact on Trust in Politicians: How Long Does It Last? - Mendiburo-Seguel, Andrés; Vargas, Salvador; Rubio, Andrés (Frontiers in Psychology, 2017)
The experimental research that looks into the effects of political humor on the individual’s attitudes towards politics and politicians does not evaluate its long-term effects. With this in mind, this study aims to determine the possible effects that being exposed to humor which belittles politicians may have on the ordinary citizen’s trust in them, while at the same time it observes the possible effects that such exposure has on them and the time such effects last. Two hypotheses were tested. The first one was that humor involves fewer cognitive elaboration which leads to a short-term impact on the perception of the individual. The second one was that the repetition of a message can augment the swing of such message. Also, a series of elements regarding disposition towards politicians and political affiliation were considered. Two experiments were designed. The first experiment, (N=94), considered three groups: one exposed to political disparagement humor; one control group exposed to disparagement humor against non-politician subjects, and a control group exposed to a non-humorous political video. Trust in politicians was evaluated first at baseline, then immediately after the experimental manipulation and once again a week after the experimental manipulation had happened. In the second experiment (N=146), participants were randomly assigned to one experimental and two control groups. The three groups were estimated in their trust in politicians and were sent political cartoons, non-political cartoons and newspaper headlines regarding political topics two times a day for a week via Whatsapp. Trust in politicians amongst the three groups was assessed again after one week, and for a third time one week after that. As a result, it was observed that a one-off exposure to political disparagement humor affects trust in politicians negatively, however, the effect it attains is short-lived and can be explained through the political content of the item and not only humor. Also, being exposed to cartoons constantly for a week had no impact whatsoever on the way politics and politicians was perceived during the time the experiment was carried out. Possible explanations to these findings are discussed.